Corneal Endothelial Cell Density and Morphology in Healthy Egyptian Eyes - Marwa Mahmoud Abdellah; Hatem Gamal Ammar; Mohamed Anbar; Engy Mohammed Mostafa; Mahmoud Mohamed Farouk; Khulood Sayed; Alahmady Hammad Alsmman; Mohamed Gamal Elghobaier (Journal of Ophthalmology)
Purpose. To evaluate the corneal endothelial cell density and morphology in normal Egyptian eyes. Methods. In total, 568 healthy eyes of 568 Egyptian volunteers aged 20 to 85 years were examined using noncontact specular microscopy for the central corneal thickness (CCT), mean endothelial cell density (MCD), coefficient of variation (CV) in cell area, mean cell area (MCA), and hexagonal cell (Hex) percentage. Variables were compared between sexes and between different age groups. Results. The mean CCT, MCD, and MCA were 514.45 ± 43.04 μm, 2647.50 ± 382.62 cells/mm2, and 390.59 ± 149.94 μm2, respectively. MCD and MCA showed no significant differences between men and women (P=0.171 and 0.099, respectively), whereas CV (%) and Hex (%) showed significant differences (P=0.024 and 0.015, respectively). CCT (P=0.007, r = −0.113) and MCD (P<0.001, r = −0.357) exhibited a significant negative correlation with age, whereas CV (%) (P<0.001, r = 0.341) and MCA (P=0.008, r = 0.111) exhibited a significant positive correlation. The mean rate of endothelial cell loss from 20 to 85 years of age was 0.3% per year. Conclusions. Our results provide normative data for the corneal endothelium in healthy Egyptian eyes, thus increasing the knowledge base for corneal endothelial cell parameters in healthy Egyptian eyes. Furthermore, our findings can be used as baseline values for comparisons between Egyptian and other populations and for studies of the endothelial cell reserve and capacity for intraocular surgery and corneal transplantation.